1988
DOI: 10.1172/jci113545
|View full text |Cite
|
Sign up to set email alerts
|

Nonbinding inhibitory antiinsulin receptor antibodies. A new type of autoantibodies in human diabetes.

Abstract: Sera and their IgG from 10/104 diabetic patients (five with insulin-dependent and five with noninsulin-dependent diabetes, NIDDM), contained antibodies that bound 125I-labeled purified human insulin receptors. 9 of these 10 sera failed to inhibit insulin binding (to rat hepatocytes and human placental membranes), did not stimulate glucose oxidation (by isolated rat adipocytes), and did not bind human placental IGF-1 receptors. Only one serum (and its IgG) modestly inhibited insulin binding and stimulated gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, in TBII-negative patients, the inhibition of TSH-stimulated iodine uptake correlated significantly with that of forskolin-stimulated iodine uptake [22]. These data may suggest that nonbinding inhibitory TSH-receptor antibodies exist, as was found in anti-insulin receptor antibodies in some patients with non-insulin dependent diabetes mellitus [2], and that these antibodies may exert an influence on a post-receptor process.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, in TBII-negative patients, the inhibition of TSH-stimulated iodine uptake correlated significantly with that of forskolin-stimulated iodine uptake [22]. These data may suggest that nonbinding inhibitory TSH-receptor antibodies exist, as was found in anti-insulin receptor antibodies in some patients with non-insulin dependent diabetes mellitus [2], and that these antibodies may exert an influence on a post-receptor process.…”
Section: Discussionmentioning
confidence: 68%
“…First, IGF-1 receptor, insulin and glucagon, all at high concentrations, did not crossreact with the antiserum when diluted 1:3000. IGF-1 receptor did, however, crossreact with the AIRA at dilutions of less than 1:500 (Boden et al 1988). Second, pure placental insulin receptor and solubilized crude human placental membranes both competed with equal potency for binding to the antiserum.…”
Section: Discussionmentioning
confidence: 93%
“…Insulin and IGF-1 receptors are similar in size and structure (LeBon et al 1986;Rechler 1985) and many antiinsulin receptor antibodies have been found to crossreact with IGF-1 receptor (Boden et al 1988;Kasuga, Sasaki, Kahn, Nissley and Rechler 1983;Roth, Maddux, Wong, Styne, Vliet, Humbel and Goldfine 1983). The-antiserum, at the dilution used in this assay, appeared to be specific for the insulin receptor as documented by 2 observations.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that heterogeneity of epitopes on the receptor to which distinct subpopulations of these antibodies bind will be shown to account for such differences in clinical outcome in individual patients. Autoantibodies to the insulin receptor are found in a small number of patients with insulinresistant diabetes, and an even smaller number of patients with unexplained hypoglycemia (15), but are not an important cause of insulin resistance in the general population (7,16).…”
Section: Insulin Resistance Due To Autoantibodies To the Insulin Recementioning
confidence: 99%